Performance Monitoring via Functional Near Infrared Spectroscopy for Virtual Reality Based Basic Life Support Training - Aksoy, Emin; Izzetoglu, Kurtulus; Baysoy, Engin; Agrali, Atahan; Kitapcioglu, Dilek; Onaral, Banu (Frontiers in Neuroscience, 2019)
The use of serious game tools in training of medical professions is steadily growing. However, there is a lack of reliable performance assessment methods to evaluate learner’s outcome. The aim of this study is to determine whether functional near infrared spectroscopy (fNIRS) can be used as an additional tool for assessing the learning outcome of virtual reality (VR) based learning modules. The hypothesis is that there would be decrease in the participants’ cerebral oxygenation levels measured from the prefrontal cortex (PFC) region and an increase of participants’ serious gaming results. To test this hypothesis, the subjects were recruited and divided into 4 four groups with different combinations of prior virtual reality experience and prior Basic Life Support (BLS) knowledge levels. A VR based serious gaming module for teaching BLS and 16-Channel fNIRS system were used to collect data from the participants. Results of the participants’ scores acquired from the serious gaming module with fNIRS measures on the initial and final training sessions were compared. Kruskal Wallis test was used to determine any significant statistical difference between the groups and Mann-Whitney U test was used to make pairwise comparisons. BLS training scores of the participants acquired from VR based serious game’s the learning management system and fNIRS measurements revealed decrease in use of resources from the PFC, but increase in behavioral performance. Importantly, brain-based measures can be used as an additional quantitative metric for trainee’s expertise development and can assist the medical simulation instructors.